The Moderating Infl uence of Trust on the Relationship between Institutional Image/Reputation, Perceived Value on Student Loyalty in Higher Education Institution - Hashim, Noor Azmi Bin; Abdullateef, Aliyu Olayemi; Sarkindaji, Bashir Danlami (International Review of Management and Marketing, 2015)
This survey investigates the moderating influence of trust on the relationships between institutional image/reputation, perceived value on student loyalty. The methodology utilises primary data obtained from questionnaire administered to a sample of 304 postgraduate international students in Universiti Utara Malaysia using simple random probability sampling. Multiple regression technique was employed to analyse data via SPSS statistical package. Results established that institutional image and perceived value have significant positive influence on student loyalty. Institutional image has significant positive influence on perceived value. The influence of image on student loyalty is greater followed by image on student perceived value. Furthermore trust was found to insignificantly moderate between institutional image and perceived value on student loyalty. It is recommended that to successfully compete in a dynamic and complex world of academic excellence universities must be seen to portray favourable image/reputation in terms of practices and actions that invariably transforms to higher perceived value and student loyalty behaviour. Keywords: Institutional Image, Perceived Value, Student Loyalty JEL Classifications: M3